Wood‐inhabiting beetles (Coleoptera) associated with oaks in a global biodiversity hotspot: a case study and checklist for Israel. Issue 6 (15th March 2013) - Buse, Jörn; Assmann, Thorsten; Friedman, Ariel‐Leib‐Leonid; Rittner, Oz; Pavlicek, Tomas; R. Leather, Simon; Ribera, Ignacio
Abstract The East Mediterranean region is a global biodiversity hotspot for vertebrates and plants. Although oaks (Quercus) are the dominant tree species in semi‐natural Mediterranean forests, the insect species richness associated with East Mediterranean oak forest has been insufficiently studied. Species richness and composition of the saproxylic beetle assemblage, including its seasonal variation, of a stand of old oaks (Quercus calliprinos) in northern Israel was investigated. Flight‐interception traps were used to sample beetles over a period of 2 years. In addition, a set of pitfall traps was placed in the trunk hollows in the second year of the study. Fifty‐two saproxylic beetle species were found associated with oaks in the field study. Among them, two saproxylic click‐beetle species were previously unknown to science, and eight species represent new records for Israel. Both the number of species and the number of individuals showed two distinct phenological peaks during the year. A preliminary list of saproxylic beetles inhabiting oaks in Israel was prepared and biogeographical distribution, host plants, habitat guild, and activity period are presented for each species. Together with our own data, the literature survey conducted for 19 beetle families established that at least 124 saproxylic beetle species are associated with oaks in Israel while about 40% of them are unique to the Levantine region. As most localities with old‐growth oak forest structures are small and isolated, ongoing management should have high priority despite the fact that these forests already receive protection.